Enhancement of oxygen reduction reactivity on TiN by tuning the work function via metal doping. Issue 48 (18th November 2022) - Chisaka, Mitsuharu; Abe, Toshiyuki; Xiang, Rong; Maruyama, Shigeo; Daiguji, Hirofumi
Abstract : A new strategy, optimising the work function via the doping of foreign metals, is revealed to enhance the oxygen reduction reactivity on TiN surface. Abstract : Oxide layers on conductive TiN have recently been investigated to catalyse the oxygen reduction reaction (ORR) in acidic media. The ORR reactivity, i.e., activity and selectivity, has been correlated with the surface nitrogen atoms. A new strategy, optimising the work function via the doping of foreign metals, is revealed herein to enhance the reactivity.